Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan, Ukuran Perusahaan Terhadap Manajemen Laba Dimoderasi Kepemilikan Manajerial - Karo, Anggelia Tesalonika Karo Karo; Syamsul Bahri Arifin; Iman Indrafana Kusuma Hasbulla (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to determine the effect of tax planning, deferred tax expense and firm size on earnings management with managerial ownership as a moderating variable in Consumer Non-Cyclical sector companies listed on the Indonesia Stock Exchange in 2018 - 2022. The sample selection method used is purposive sampling. The total observations obtained in this study were 155 observations consisting of 31 companies. The data analysis technique used in this study is moderation analysis with the Moderated Regression Analysis approach or interaction test with an analysis tool using SPSS version 26. The results of this study indicate that tax planning and deferred tax expense have no effect on earning management, but firm size has an effect on earning management. The results of the moderation analysis test show that managerial ownership is unable to moderate the effect of tax planning on earning management, but managerial ownership is able to moderate the deferred tax expense and firm size on earning management in Consumer Non-Cyclicals sector companies listed on the IDX.